Towards Capturing Security Requirements in Agile Software Development - Ahmed, W.; Hafeez, Y.; G. Chiurlea, G. (The Nucleus, 2017)
Software use is an unavoidable reality. Increased use expands the opportunity for malicious use which threatens security and privacy. There are many factors like data loss, increase in budget cost due to security breaches, pending legislation and competitive advantage are driving software developers to integrate security into software development rather than adding security in later stages of development. The approach presented here addresses elicitation, prioritization, analysis of requirements and security requirements. This can be done by identifying candidate’s security goals, their categorization and understanding with stakeholders to develop preliminary security requirements and then prioritization and at the end security requirements are output.